Addressing obesity in Roma communities: a community readiness approach. Issue 2 (18th October 2018) - Islam, Shahid; Small, Neil; Bryant, Maria; Yang, Tiffany; Cronin de Chavez, Anna; Saville, Fiona; Dickerson, Josie
Abstract : Purpose: Participation in community programmes by the Roma community is low, whilst this community presents with high risk of poor health and low levels of wellbeing. To improve rates of participation in programmes, compatibility must be achieved between implementation efforts and levels of readiness in the community. The Community Readiness Model (CRM) is a widely used toolkit which provides an indication of how prepared and willing a community is to take action on specific issues. The purpose of this paper is to present findings from a CRM assessment for the Eastern European Roma community in Bradford, UK, on issues related to nutrition and obesity. Design/methodology/approach: The authors interviewed key respondents identified as knowledgeable about the Roma community using the CRM. This approach applies a mixed methodology incorporating readiness scores and qualitative data. A mean community readiness score was calculated enabling researchers to place the community in one of nine possible stages of readiness. Interview transcripts were analysed using a qualitative framework analysis to generate the contextual information. Findings: An overall score consistent with vague awareness was achieved, which indicates a low level of community readiness. This score suggests that there will be a low likelihood of participation in currently available nutrition and obesity programmes. Originality/value: To our knowledge, this is the first study to apply the CRM in the Roma community for any issue. The authors present the findings for each of the six dimensions that make up the CRM together with salient qualitative findings.